2007
DOI: 10.1074/jbc.m610432200
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Mechanisms for CCN2/CTGF Persistence in Fibrotic Gingiva

Abstract: Prostaglandin E 2 blocks transforming growth factor TGF ␤1-induced CCN2/CTGF expression in lung and kidney fibroblasts. PGE 2 levels are high in gingival tissues yet CCN2/CTGF expression is elevated in fibrotic gingival overgrowth. Gingival fibroblast expression of CCN2/CTGF in the presence of PGE 2 led us to compare the regulation of CCN2/CTGF expression in fibroblasts cultured from different tissues. Data demonstrate that the TGF␤1-induced expression of CCN2/CTGF in human lung and renal mesangial cells is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 63 publications
(62 reference statements)
2
33
0
Order By: Relevance
“…TGF␤1 and LPA Stimulate Similar Levels of JNK1 Phosphorylation in Human Gingival Fibroblasts-We previously demonstrated that JNK1 phosphorylation induced by TGF␤1 is essential for maximal CCN2/CTGF expression (40). We hypothesize that, like TGF␤1, LPA might stimulate JNK1 activation.…”
Section: Kinetics Of Ccn2/ctgf Mrna and Protein Expression Differ Inmentioning
confidence: 89%
See 4 more Smart Citations
“…TGF␤1 and LPA Stimulate Similar Levels of JNK1 Phosphorylation in Human Gingival Fibroblasts-We previously demonstrated that JNK1 phosphorylation induced by TGF␤1 is essential for maximal CCN2/CTGF expression (40). We hypothesize that, like TGF␤1, LPA might stimulate JNK1 activation.…”
Section: Kinetics Of Ccn2/ctgf Mrna and Protein Expression Differ Inmentioning
confidence: 89%
“…Activation of the c-Jun N-terminal kinase 1 (JNK1) is essential for maximal expression of CCN2/CTGF in response to TGF␤1 in gingival fibroblasts (40). We hypothesized that Rho family GTPases were required in mediating the TGF␤1-induced activation of JNK.…”
Section: Kinetics Of Ccn2/ctgf Mrna and Protein Expression Differ Inmentioning
confidence: 99%
See 3 more Smart Citations